Clinical characteristics, predictors and outcome of children with complicated parapneumonic effusion: a single centre experience - Hasniah Abdul Latif,; Nur Azah MI,; Faizah MZ, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Parapneumonic effusions (PPE) is a complication of bacterial pneumonia. Factors that contribute to complicated PPE remain uncertain. This study was aimed to describe the characteristics, clinical predictors and outcome of children with parapneumonic effusion (PPE) in Universiti Kebangsaan Malaysia Medical Centre (UKMMC). A retrospective study on children with PPE who were admitted to UKMMC between January 2010 to December 2017 was conducted. Patients were categorised into 2 groups: simple and complicated PPE. Of 45 patients recruited, 20 (44.4%) patients had simple PPE and 25 (55.6%) had complicated PPE. Their median age was 32 months (IQR 16-63). The most common isolated organism was Streptococcus pneumoniae (61.9%), followed by Mycoplasma pneumoniae (19.0%) and Staphylococcus aureus (4.8%). Only 11.1% of patients received pneumococcal vaccination. There was no statistical significant difference in clinical features between simple and complicated PPE. Only 62.2% patients had ultrasound thorax done. Majority (95.0%) of patients with simple PPE were successfully treated with intravenous antibiotics alone. Sixty percent of patients with complicated PPE needed surgical intervention. Mean length of hospital stay for simple PPE was 10 (4.0) days and complicated PPE was 28 (16.5) days. In conclusion, clinical features could not predict complicated PPE. Use of ultrasound thorax as the main investigation tool for diagnosis and staging should be emphasised. Antibiotics therapy alone is effective therapy for simple PPE, while in complicated PPE, larger prospective studies are required to investigate which children benefit significantly from more intensive intervention.